2020
DOI: 10.1103/physrevlett.124.088301
|View full text |Cite
|
Sign up to set email alerts
|

Birth and Stabilization of Phase Clusters by Multiplexing of Adaptive Networks

Abstract: We propose a concept to generate and stabilize diverse partial synchronization patterns (phase clusters) in adaptive networks which are widespread in neuro-and social sciences, as well as biology, engineering, and other disciplines. We show by theoretical analysis and computer simulations that multiplexing in a multi-layer network with symmetry can induce various stable phase cluster states in a situation where they are not stable or do not even exist in the single layer. Further, we develop a method for the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 103 publications
0
47
0
Order By: Relevance
“…Several studies have shown that multiplex networks can generate patterns with significant differences from those observed in single-layer networks (Kouvaris et al, 2015 ; Majhi et al, 2016 , 2017 ; Berner et al, 2020 ). Their use in the optimization and control of dynamical behaviors have therefore attracted much attention recently.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that multiplex networks can generate patterns with significant differences from those observed in single-layer networks (Kouvaris et al, 2015 ; Majhi et al, 2016 , 2017 ; Berner et al, 2020 ). Their use in the optimization and control of dynamical behaviors have therefore attracted much attention recently.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex networks can be associated with social and technological systems, 20 for instance, with dynamical processes where layers correspond to the states of the system at different times, 21 or with different types of links. Multilayer structures allow for full 22 or partial 23 synchronization between the layers, and different synchronization scenarios can be observed, such as explosive synchronization. 24…”
Section: Introductionmentioning
confidence: 99%
“…It drastically simplifies the problem by reducing the dimension and unifying the synchronization study for different networks. Since its introduction, the master stability approach has been extended and refined for multilayer [39], multiplex [40,41] and hypernetworks [42,43]; to account for single and distributed delays [44][45][46][47][48][49]; and to describe the stability of clustered states [50][51][52][53]. The master stability function has been used to understand effects in temporal [54,55] as well as adaptive networks [56] within a static formalism.…”
mentioning
confidence: 99%
“…Moreover, adaptive networks have been reported for chemical [67,68], epidemic [69], biological [70], transport [71], and social systems [72,73]. A paradigmatic example of adaptively coupled phase oscillators has recently attracted much attention [12,41,[74][75][76][77][78][79][80][81], and it appears to be useful for predicting and describing phenomena in more realistic and detailed models [82][83][84][85]. Systems of phase oscillators are important for understanding synchronization phenomena in a wide range of applications [86][87][88].…”
mentioning
confidence: 99%
See 1 more Smart Citation